1997
DOI: 10.4294/jpe1952.45.167
|View full text |Cite
|
Sign up to set email alerts
|

Uplift and Tectonics of the Shillong Plateau, Northeast India.

Abstract: Different views prevail regarding the uplift and tectonics of the Shillong Plateau in northeastern India. In light of these, we discuss the cause of the current uplift, the time of initiation of the uplift, and the current tectonic scenario. Various geophysical results indicate that neither a thermal anomaly nor isostatic compensation could have caused the uplift as suggested by many workers in the past. Several coinciding factors point towards a combination of tectonic forces in this unique thrust environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 14 publications
(18 reference statements)
1
25
0
Order By: Relevance
“…All these arguments point towards a high‐velocity, cold, upper mantle, suggesting that a thermal source due to an earlier hotspot or plume activity, could not have caused the current uplift. Based on the analysis of focal mechanisms and computation of strain rates, a new model for the uplift of the Shillong plateau has been proposed (Rao & Kumar 1997). It is suggested that the Shillong plateau was uplifted under the influence of compressive stresses resulting from the India‐‐Eurasia collision in the North, aided by a timely impetus from the India‐‐Burma thrust forces in the east, which is sustained even at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these arguments point towards a high‐velocity, cold, upper mantle, suggesting that a thermal source due to an earlier hotspot or plume activity, could not have caused the current uplift. Based on the analysis of focal mechanisms and computation of strain rates, a new model for the uplift of the Shillong plateau has been proposed (Rao & Kumar 1997). It is suggested that the Shillong plateau was uplifted under the influence of compressive stresses resulting from the India‐‐Eurasia collision in the North, aided by a timely impetus from the India‐‐Burma thrust forces in the east, which is sustained even at present.…”
Section: Discussionmentioning
confidence: 99%
“…These uplifted regions along with the ‘foreland spur’ represent the northeastern extension of the Indian shield elements (Nandy 2001) whose basement is comprised of Archaean gneissic rocks. Various hypotheses have been proposed to explain the Shillong uplift, which include isostatic adjustment (Das Gupta & Biswas 2006), thermal disturbance during Jurassic, which resulted in uplift that is still continuing (Kailasam 1979) and pop‐up due to tectonic forces (Rao & Kumar 1997; Bilham & England 2001). Also, two prominent faults to the south of the Shillong plateau acted as vents to the eruption of Sylhet traps about 116 Ma (Ray et al 2005), as a consequence of the heating of the Indian Plate as it passed over the Kerguelen hotspot (Kumar et al 2004a).…”
Section: Study Regionmentioning
confidence: 99%
“…They further suggested that the plateau earthquakes are generated by 'pop-up' tectonics between the two boundary faults, the Dauki fault and the Oldham fault. Rao and Kumar (1997) first proposed the pop-up tectonics for the Shillong plateau, and they suggested that the pop-up mechanism is facilitated by the Dauki fault to the south, Brahmaputra fault to the north, Dhubri fault to the west and Disang thrust to the east (figure 9). Bilham and England (2001), however, illustrated a quantitative model of the Shillong plateau pop-up tectonics for the 1897 great earthquake ( figure 11(a)).…”
mentioning
confidence: 99%
“…The western boundary of the Plateau is characterized by a north-south trending Dhubri fault. Rao and Kumar (1997) first proposed the pop-up tectonics for the Shillong Plateau, and they suggested that the pop-up mechanism is facilitated by the Dauki fault to the south, Brahmaputra fault to the north, Dhubri fault to the west and Disang thrust to the east. However, Bilham and England (2001), based on geodetic and GPS data, illustrated a quantitative model of the Shillong Plateau pop-up tectonics between the proposed south dipping hidden Oldham fault and the north dipping Dauki fault.…”
Section: Tectonic Setting Of the Regionmentioning
confidence: 98%
“…The Shillong Plateau in the NER, India is a part of the Indian shield that is separated out from the peninsular shield and moved to the east by about 300 km along the Dauki fault (Evans, 1964). The Shillong Plateau was uplifted during the latest Cenozoic (Rao and Kumar, 1997). The E-W trending Dauki fault separates the Plateau to the north and the Bengal basin to the south.…”
Section: Tectonic Setting Of the Regionmentioning
confidence: 98%